The impact of work-life balance, work safety, and workload on employee retention in Indonesia's port industry - Jennifer Collin Suprapto; Puput Marshanda; Betric Nandela, Fransisca; Siddiq , Dedi Muhammad (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The purpose of this study is to examine how employee retention in Indonesian ports is impacted by workload, work-life balance, and safety. The study makes use of primary data and a quantitative methodology. The study's 200 participants are Pelabuhan Indonesia employees. Saturated samples, or sampling strategies that use the entire population as a sample, are the method used in this study. Questionnaires are used to collect data. According to the study's findings, (1) workload is somewhat positively correlated with employee retention (tcalculate > ttable), meaning that (3.261 > 1.65259), with a significance level of 0.01. (2) With a significance level of 0.012, partial work balance has a positive impact on employee retention (tcount > ttable), resulting in (2.533 > 1.6529). (3) There is a partial positive relationship between work safety and employee retention (tcalculate > ttable), resulting in (2.414 > 1.6529) with a significance level of 0.017. (4) Employee retention (Fhitung>Ftabel), or (10.261 > 3.04), is influenced (simultaneously) by workload, work balance, and work safety, with a significance level of 0.000 < 0.05. Based on the research findings, it can be inferred that the workload variable positively affects employee retention in the Port of Indonesia company, as does work balance